PENGARUH KINERJA DAN UKURAN PERUSAHAAN TERHADAP STOCK RETURN PERUSAHAAN NON KEUANGAN DI INDONESIA - SANTOSO CHANDRA; CINDY FRANSISCA (E-Jurnal Akuntansi TSM, 2021)
This study is made in a purpose to gain more of an empirical evidence about the factors that affect stock return of corporations listed in Indonesian Stock Exchange. This study uses independent variables which are quick ratio, earnings per share, return on equity, net profit margin, debt to equity ratio, company size, market value added, price to book value and total asset turnover. This study uses samples from non-financial corporations listed in Indonesian Stock Exchange during the period 2017 to 2019. The method used to obtain samples is purposive sampling method, there are 249 companies that meet the criteria and used as samples. The process of data analysis method used in this study is multiple regression of analysis. The results of this study indicate that return on equity have influence to stock return, while quick ratio, earnings per share, net profit margin, debt to equity ratio, company size, market value added, price to book value and total asset turnover have no impact or influence to stock return